2018
DOI: 10.1016/j.heliyon.2018.e00821
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility of Shore Magic® collagen, a low-molecular-weight collagen supplement, in different in vitro barrier models

Abstract: Hydrolyzed collagen consists of peptides, which exert important biological functions in different body systems. This study aimed at testing the biological effects of a low molecular weight collagen (LMWC), namely Shore Magic® Collagen (SMC), in a series of in vitro assays and three different in vitro barrier models with translational significance. We also compared SMC's biological activities with its trypsinized form (TSMC). SMC enhanced migration in both epithelial and endothelial cells; and increased the adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Lower molecular weight molecules could penetrate into cells better than a higher molecular weight molecule, therefore leading to better cell or tissue functional improvement [59]. Furthermore, many studies have found that collagen with molecular weights of less than 5 kDa can increase cell proliferation, migration, adhesion, anti-oxidization, or angiotensin-I converting enzyme (ACE) inhibition activity [36,60,61,62]. Therefore, the molecular weight of collagen could be considered as a significant factor for collagen selection.…”
Section: Resultsmentioning
confidence: 99%
“…Lower molecular weight molecules could penetrate into cells better than a higher molecular weight molecule, therefore leading to better cell or tissue functional improvement [59]. Furthermore, many studies have found that collagen with molecular weights of less than 5 kDa can increase cell proliferation, migration, adhesion, anti-oxidization, or angiotensin-I converting enzyme (ACE) inhibition activity [36,60,61,62]. Therefore, the molecular weight of collagen could be considered as a significant factor for collagen selection.…”
Section: Resultsmentioning
confidence: 99%
“…On the 7 th day, the angiogenesis phase reaches its peak. [ 2 3 ] It is also known that healing process is influenced by systemic factors, one of which is comorbidities, such as diabetes mellitus (DM). DM is known to cause macrophage dysfunction in the patients.…”
Section: Introductionmentioning
confidence: 99%